Advertisement call, colour variation, natural history, and geographic distribution of Proceratophrys caramaschii (Anura: Odontophrynidae) - Nunes, Ivan; Loebmann, Daniel; Cruz, Carlos Alberto G.; Haddad, Celio F. B. [UNESP] (Deutsche Gesellschaft Herpetologie Terrarienkunde E V, 2015)
Proceratophrys caramaschii was described only from a single locality in Mucuripe, Fortaleza municipality, Ceara state, Brazil. The discovery of a new population of this poorly known species facilitated the collection of new data regarding colour in life, vocalization, habitat, and geographic distribution. It has a much wider distribution than formerly thought, is considerably variable in its colour pattern, and its reproductive strategy is strongly associated with the beginning of the rainy season. Males call from the ground and hidden in vegetation. The advertisement call is a short trill of notes. Further data is necessary to evaluate the threat status of this species.
Keywords: Amphibia; Anura; Proceratophrys; Antiphonal call; Colour variation; Biology; Caatinga Domain